Harnessing Serious Games For Developing Indonesian Elementary School Students’ Critical Thinking Attitudes - Asep Nuryadin; Dessy Nur Amelia; Sani Aryanto (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2022)
Critical thinking is one of the essential skills required in all fields in the 21st century. As a response to this need, one of the efforts that Indonesian policy-makers make is through developing Curriculum 2013 which is designed to equip students with the ability to think critically. However, instilling critical thinking skills from an early age without developing an individual’s critical thinking attitudes is not a wise choice. It is because possessing critical thinking skills without having a willingness to use them will be less beneficial. This article presents the results of a literature study on how serious games, as a product of current advancement of digital technology, can be utilised to develop three critical thinking attitudes, namely, willingness to plan, the attitude of flexibility, and consensus-seeking attitude. Moreover, this article also presents three strategies that can be used to implement serious games in Indonesian elementary school context, namely, using ADDIE (analysis, design, development, implementation, and evaluation) model as a framework for developing serious games, adapting the existing serious games with BYOD (bring your own device) model, and promoting parental and family involvement.